Characterization of Ascaris from Ecuador and Zanzibar. Issue 4 (July 2015) - Sparks, A.M.; Betson, M.; Oviedo, G.; Sandoval, C.; Cooper, P.J.; Stothard, J.R.
Abstract To shed light on the epidemiology of ascariasis in Ecuador and Zanzibar, 177 adult worms retrieved by chemo-expulsion from either people or pigs were collected, measured and subjected to polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) analysis of the ribosomal internal transcribed spacer (ITS) region. Upon double digestion with RsaI and HaeIII, PCR-RFLP analysis revealed the presence of A. lumbricoides in people and A. suum in pigs in Ecuador. In contrast, while there are no pigs on Zanzibar, of the 56 worms obtained from people, one was genotyped as A. suum. No additional genetic variation was detected upon further PCR-RFLP analysis with several other restriction enzymes. Upon measurement, worm mass and length differed by location and by species, A. suum being lighter and longer. While there is no evidence to suggest zoonotic transmission in Ecuador, an enduring historical signature of previous zoonotic transmission remains on Zanzibar.